2018
DOI: 10.1029/2018wr023189
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Orientation of Maximum Permeability and Intermediate Principal Stress in Fractured Rocks

Abstract: Flow and transport properties of fractured rock masses are a function of geometrical structures across many scales. These structures result from physical processes and states and are highly anisotropic in nature. Fracture surfaces often tend to be shifted with respect to each other, which is generally a result of stress‐induced displacements. This shift controls the fracture's transmissivity through the pore space that forms from the created mismatch between the surfaces. This transmissivity is anisotropic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 101 publications
(180 reference statements)
0
18
0
Order By: Relevance
“…An increased normal stress may lead to a decreased fracture aperture and permeability, while an increase in shear stress can cause dilational displacement and enhance permeability (Barton et al, ; Lei et al, ; Min et al, ). In such deep crustal systems, the correlation between stress and permeability may be observed (Lang et al, ; Rutqvist & Stephansson, ). However, stress effects on the permeability of fractures in shallow crystalline rocks recently have been shown to be minor based on hydraulic tests at low pressure (Mattila & Follin, ).…”
Section: Discussionmentioning
confidence: 99%
“…An increased normal stress may lead to a decreased fracture aperture and permeability, while an increase in shear stress can cause dilational displacement and enhance permeability (Barton et al, ; Lei et al, ; Min et al, ). In such deep crustal systems, the correlation between stress and permeability may be observed (Lang et al, ; Rutqvist & Stephansson, ). However, stress effects on the permeability of fractures in shallow crystalline rocks recently have been shown to be minor based on hydraulic tests at low pressure (Mattila & Follin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous permeability changes along the Huarongshan fault and the anisotropy at a given well location after the Xingwen M 5.7 earthquake may be related to the heterogeneous fracture development and background tectonic stress. Field observations and simulations have shown that fault zones appear to be more permeable in areas where tectonic activity is frequent, with fissured media that are most aligned with the direction of maximum horizontal stress or that have a high ratio of shear stress to normal stress, generally exhibiting permeability (Barton et al, ; Hennings et al, ; Lang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid boundary effects, averages for equations and are computed only on elements with barycenters located within the central 90% of the domain. This approach has been referred to as undersampling or flow jacketing (Lang et al, ) and produces results which better reflect the overall connectivity of the domain (Lang et al, ). Use of Darcy's law assumes that the medium can be replaced by an equivalent homogeneous block of a small size with permeability k , known as a representative elementary volume.…”
Section: Methodsmentioning
confidence: 99%
“…The methods by which mechanical and hydraulic properties are calculated on DFNs vary widely between implementations, including boundary element (Tuckwell et al, ), discrete element (Lisjak & Grasselli, ), finite difference (Karimi‐Fard et al, ), finite element (Kim & Deo, ; Lang et al, ), finite volume (Koudina et al, ), and virtual element methods (Benedetto et al, ). Combined methods incorporate both continuum and discontinuum approaches to handle solution of forces and displacements, and handling of dynamics and contact, respectively (e.g., Elmo & Stead, ; Lisjak et al, ; Marschall et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation